60‐2: Improving LCD Contrast Ratio by Modifying Metal Layout Design. Issue 1 (2nd June 2017) - Chen, Li-Xuan; Zhang, Chao; Li, Ming-Hui; Liu, Hsiang-Chi; Chen, Hsiao-Hsien; Lee, Yung-Jui
Abstract : We have analysed and simulated light leakage in LCD caused by metal lines in pixel area. Electric field of incident linear polarized light has a projection on the junction area and stimulates SPPs mode thus transmitted light will have a different polarization direction.